Circadian pacemaking in cells and circuits of the suprachiasmatic nucleus - Hastings,MH; Brancaccio,M; Maywood,ES (Journal of Neuroendocrinology, 2014)
The suprachiasmatic nucleus (SCN) of the hypothalamus is the principal circadian pacemaker of the brain. It coordinates the daily rhythms of sleep and wakefulness, as well as physiology and behaviour, that set the tempo to our lives. Disturbance of this daily pattern, most acutely with jetlag but more insidiously with rotational shiftwork, can have severely deleterious effects for mental function and longterm health. The present review considers recent developments in our understanding of the properties of the SCN that make it a robust circadian timekeeper. It first focuses on the intracellular transcriptional/ translational feedback loops (TTFL) that constitute the cellular clockwork of the SCN neurone. Daily timing by these loops pivots around the negative regulation of the Period (Per) and Cryptochrome (Cry) genes by their protein products. The period of the circadian cycle is set by the relative stability of Per and Cry proteins, and this can be controlled by both genetic and pharmacological interventions. It then considers the function of these feedback loops in the context of cytosolic signalling by cAMP and intracellular calcium ([Ca2+]i), which are both outputs from, and inputs to, the TTFL, as well as the critical role of vasoactive intestinal peptide (VIP) signalling in synchronising cellular clocks across the SCN. Synchronisation by VIP in the SCN is paracrine, operating over an unconventionally long time frame (i.e. 24 h) and wide spatial domain, mediated via the cytosolic pathways upstream of the TTFL. Finally, we show how intersectional pharmacogenetics can be used to control Gproteincoupled signalling in individual SCN neurones, and how manipulation of Gq/[Ca2+]isignalling in VIP neurones can reprogramme the circuitlevel encoding of circadian time. Circadian pacemaking in the SCN therefore provides an unrivalled context in which to understand how a complex, adaptive behaviour can be organised by the dynamic activity of a relatively few gene